Estratégias sustentáveis para uma economia criativa responsável: m estudo sobre práticas ESG em grandes eventos no eixo São Paulo - Rio de Janeiro/Brasil - Rodrigues, Renan França dos Santos (2023)
Society is going through changes. We went through a huge health crisis that scared and changed the way we face reality during the covid-19 pandemic. New studies point to new crises due to climate change and exacerbated consumption of natural resources. A change in consumption patterns is becoming increasingly necessary. new forms of development are being studied and proposed, finding in the Creative Economy a path to the so-called Sustainable Development. This study is focused on the sector of mega events and focuses on new forms of management for this sector that is so well known and recognized for moving people and at the same time exploiting its workers. given this scenario, this dissertation aims to analyze the process that has led members of the ecosystem of major events in Rio de Janeiro and São Paulo to choose management practices aligned with ESG practices, E, from the English environment, which in Portuguese refers to practices related to the environment; the abbreviation S in English, social, which is written in the same way in Portuguese and is related to social practices; and put an end to the initials G, for governance. First, a bibliographical and secondary data survey was carried out on Creative Economy, Sustainable Development, Corporate Social Responsibility (CSR), Shared Value Creation (CVC) and the scenarios of major events after the sector's resumption. The next step to carry out such an analysis was to interview seven agents of the ecosystem of the major events in the cities of Rio de Janeiro and São Paulo in depth through a semi-structured research script addressing their levels of knowledge about ESG, main difficulties and opportunities for implementation of practices, main actions implemented and possible scenarios for the future of the ESG theme in large events. As a result, it was possible to identify that ESG practices are on the agenda of large companies and boards, but need long-term planning to be disseminated to other sectors of the event ecosystem. It became clear that a great opportunity is the interest of the sponsors in the subject and how difficult the issues of financial investment, changes in organizational culture and greenwashing. Finally, it was possible to make a practical contribution to managers of large events by identifying the main successful ESG practices that were divided into: ESG Policies, Social Practices, Certifications and Events as an Education Platform